FOLKLORE AND ITS INFLUENCE ON HOMOPHOBIC BEHAVIOUR IN THE ZULU CULTURE: A BRIEF ANALYSIS OF UMAMBA KAMAQUBA - Masuku, N (Southern African Journal for Folklore Studies, 2016)
This article argues that South African society is not receptive to gays and lesbians although South Africa is regarded as the country that has the most liberal constitution, especially when it comes to gay and lesbian rights. The rejection could be ascribed to various factors such as the socialisation of individuals. Young boys and girls are raised to understand that their destiny is to get married and bear children. In Zulu society, unmarried people are stigmatised by name-calling. There is a lot of research that has been undertaken on homosexuality and lesbianism. Mkasi (2013) discussed homosexuality amongst izangoma. Ngcobo (2007) undertook this study to describe the difficulties faced by homosexual students, their perception and understanding of social discrimination. The socio-cultural theory has been applied to re-enforce the argument. This research article highlights the argument that folklore in the form of folktales are used as a conduit to socialise the growing mind to accept that everyone is destined to marry and bear children. Anybody who deviates from this set of norms should be ostracised and punished.Â Such deep-rooted perceptions contribute to homophobia and violence against gays and lesbians.Â